Síndrome inflamatória multissistêmica pediátrica (SIM-P) temporalmente associada à Covid-19: estudo transversal dos casos e fatores associados no Ceará, 2020 a 2021 - Soares, Simone Dantas (2023)
Introduction: children and adolescents, in general, manifest mild symptoms of covid-19. However, they may develop a late and exacerbated inflammatory response after infection with covid-19, characterized as SIM-P temporally associated with covid-19. Objective: to analyze the occurrence of SIM-P cases, temporally associated with covid-19, in the State of Ceará. Methodology: this was a cross-sectional study of a secondary database containing 82 cases of children and adolescents reported with SIM-P associated with covid-19, in the State of Ceará, from 2020 to 2021. RStudio was used ®, for data calculation, considering a significance of 5% and confidence intervals of 95%. For variables with p-value less than 0.05, multivariate analysis was performed. Results: were more severe: adolescents aged 10 to 14 years (PR= 1.07; 95%CI: 1.00 – 1.15), females (PR= 1.05; 95%CI: 0.95 – 1.17), white skin color (PR= 1.09; 95%CI: 0.99 – 1.20), residents of municipalities in the interior of Ceará (PR= 1.03; 95%CI: 0.93 – 1.13), notified by public health services (RP= 1.12; 95%CI: 0.96 – 1.30), with hospitalizations longer than 10 days (RP= 1.05; 95%CI: 0.99 – 1.10), mean of 36 days between admission and notification, with admission to the ICU (PR= 1.01; 95%CI: 0.84 – 1.22). Regarding signs and symptoms, severity was associated with dyspnea (PR= 1.09; 95%CI: 1.00 - 1.18), cough (PR= 1.07; 95%CI: 1.00 - 1.14 ), myalgia (PR= 1.06; 95% CI: 1.00 - 1.13), tachycardia (PR= 1.06; 95% CI: 1.00 - 1.12), oxygen saturation below 95% in room air (PR= 1.06; CI95%: 1.00 - 1.12), lymphadenopathy (PR= 1.06; CI95%: 1.00 - 1.12), oliguria (PR= 1.06; CI95 %:1.00 - 1.12), sore throat (PR= 1.06; CI95%:1.00 - 1.11), pain on swallowing (PR= 1.05; CI95%:1.00 - 1.11), mental confusion (PR= 1.05; 95%CI: 1.00 - 1.11) and conjunctivitis (PR= 1.01; 95%CI: 0.90 - 1.12). Lethargy showed the greatest association (PR= 0.77; 95%CI: 0.52 - 1.15; p=0.048). Aspects related to laboratory tests and treatment showed the following prevalence: detection for SARS-CoV-2 by RT-PCR (PR= 1.08; 95%CI: 0.97 - 1.21) and serology (PR= 1.24 95%CI: 0.70 - 2.23); changes in NT-ProBNP (PR= 1.71; CI95%: 0.41 - 7.08), procalcitonin (PR= 1.33; CI95%: 0.76 - 2.35), ESR (PR= 1. 26; CI95%: 0.71 - 2.25), troponin (PR= 1.2; CI95%: 0.93 - 1.55), fibrinogen (PR= 1.15; CI95%: 0.95 - 1 .41), DHL (PR= 1.13; 95%CI: 0.96 - 1.32), TGO (RP= 1.1; 95%CI: 0.99 - 1.22), imaging tests with infiltrate ( PR= 1.06; 95%CI: 1.00 - 1.12), ground-glass image (PR= (RP= 1.06; 95%CI: 1.00 - 1.12), ascites (PR= 1, 05; CI95%: 1.00 - 1.11), hepatomegaly (PR= 1.05; CI95%: 1.00 - 1.11) and myocardial dysfunction (PR= 1.06; CI95%: 1.00 - 1.12); treatment with corticosteroids (PR= 1.14; CI95%: 0.89 - 1.45) and systemic anticoagulation (PR= 1.11; CI95%: 0.99 - 1.25). Death (PR= 1.05; 95%CI: 0.99 - 1.10), hospital discharge without sequelae (PR= 1.04; 95%CI: 0.99 - 1) was also associated with higher prevalence rates. .09) and closure of cases according to laboratory criteria (PR= 1.27; 95%CI: 0.89 - 1.80). Conclusion: the data presented provide subsidies for the early diagnosis of this syndrome, allowing the reduction of negative outcomes and its better prognosis.